Role of parents who work as teachers in supporting their success study in the Perumnas Belimbing village Kuranji Padang town. - Agustia, Desy; Basri, Wahidul; Erningsih, Erningsih (Pendidikan Sosiologi, 2014)
Family is one of the important factors in determining the success of a child . family is first and foremost a place of education for every child , also act as teachers and mentors . the role of parents is crucial to the success of childrens learning coloring to achieve the goal of National. Studied in this research is the role of parents who work as teachers in supporting their success in learned at Perumnas Belimbing Kuranji. Background of this research there are some childrens whose parents work as teachers do not get more attention is because her parents are always busy teaching, and beside teaching the parents who are teachers working as a merchant so the lack of time to control the child, the formulation the problem is how the role of a parent who is a teacher in supporting their children learning success at the Perumnas Belimbing, while the purpose of this study was to reveal the role of parents who work as teachers in supporting their learning success. Theory used is a functional of structural Robert K.Merton focused role that parents who are teachers have consequences social. Consequence objectives of the objectives of the system arising from the actions committed by parents in fulfilling the role of the family may be a consequence of manifest or latent consequences . This research used a qualitative approach with descriptive type , data collection by observation and in-depth interviews nonparticipation. This research uses 12 parents who work as teachers and 3 childrens. informan of this research there were 15 people who were interviewed about the role of parents who work as teachers in supporting their learning success at Perumnas Belimbing. Data analysis is a model of Miles and Huberman, data presentation and conclusion. Field findings indicate that parents who work as teachers have role in the success of their learning, although there are some parents who do not have time to meet with their children and supervise their children in after-school study due to fatigue because the parents taught him distant place, the role of parents worked as a teacher can be seen from its role in instilling a love of science to their children, guiding and directing supervise children in their homework, pick a good teacher and a good school, making the reading room in their house. And parents who are teachers still spend time to control their children.